1999
DOI: 10.1007/s11745-999-0369-5
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid ingestion inhibits natural killer cell activity and production of inflammatory mediators in young healthy men

Abstract: The purpose of this study was to examine the effects of feeding docosahexaenoic acid (DHA) as triacylglycerol on the fatty acid composition, eicosanoid production, and select activities of human peripheral blood mononuclear cells (PBMNC). A 120-d study with 11 healthy men was conducted at the Metabolic Research Unit of Western Human Nutrition Reach Center. Four subjects (control group) were fed the stabilization diet throughout the study; the remaining seven subjects were fed the basal diet for the first 30 d,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
139
2
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(158 citation statements)
references
References 41 publications
11
139
2
6
Order By: Relevance
“…Most of these studies, however, were small and used fish oil, with little attention given to specific DHA effects. Our findings do agree with data from in vitro studies, particularly from cultured cells, including monocytes and endothelial cells 77, 78, 79, 80. We thus conclude that the atheroprotective effect of DHA is transduced by alterations in flow leading to an arterial environment in which levels of these plasma chemoattractants are reduced.…”
Section: Discussionsupporting
confidence: 90%
“…Most of these studies, however, were small and used fish oil, with little attention given to specific DHA effects. Our findings do agree with data from in vitro studies, particularly from cultured cells, including monocytes and endothelial cells 77, 78, 79, 80. We thus conclude that the atheroprotective effect of DHA is transduced by alterations in flow leading to an arterial environment in which levels of these plasma chemoattractants are reduced.…”
Section: Discussionsupporting
confidence: 90%
“…The relative resistance of immune cells to change in DHA content is reported by others [23][24][25] . The FA composition of immune cell phospholipids may not alter as much as blood lipid pools because these cells exert a significant level of control over their plasma membrane composition 26 .…”
Section: Discussionsupporting
confidence: 57%
“…It is for this reason that we were interested in the time course of FA composition changes, because it may be desirable in some clinical settings to provide n-3 FAs quickly. The main clinical outcomes from this trial have been published recently 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the effects of long-chain n-3 PUFA on NK cell activity remain unclear and the inconsistency has only increased with this recent report. Previous suggestions that 'high' but not 'low' doses of DHA can decrease NK cell activity (Kelley et al 1999;Thies et al 2001b) and that cells from older subjects might be more susceptible to the effects of EPA and DHA than those of young subjects (Calder, 2001a) are not rejected by the recent data. Again, it would be useful to conduct a well-powered study comparing the effects of long-chain n-3 PUFA on NK cell activity in young and older subjects.…”
Section: Effects Of Epa and Dha On Natural Killer Cell Activitymentioning
confidence: 78%
“…7 g DHA/d in elderly subjects. Kelley et al (1999) have reported inhibition of NK cell activity following 6 g DHA/d in young males. In contrast, Yaqoob et al (2000) have found no effect of 3 .…”
Section: Effects Of Epa and Dha On Natural Killer Cell Activitymentioning
confidence: 99%